An Evaluation of the Implementation of Personal Development Planning - Ioanna Palaiologou (Educational Futures)
This paper aims to explore the role of personal development planning (PDP) tutorials in non-QTS Education Studies degrees. PDP tutorials were implemented in order to help students improve their academic skills and to enhance their employability. Based on an evaluation of the PDP tutorials by students over a period of three years and through interviews with academic staff, this paper investigates the role of PDP tutorials in supporting those students.